Respuesta :

Answer:

f^-1(x) = 9(x+2)

Step-by-step explanation:

To find the inverse function, exchange x and y and then solve for y

y = 1/9 x -2

Exchange x and y

x = 1/9 y-2

Solve for y

Add 2 to each side

x+2 = 1/9 y-2+2

x+2 = 1/9y

Multiply each side by 9

9(x+2) = 9*1/9y

9(x+2) = y

The inverse function

f^-1(x) = 9(x+2)

Answer:

9x+18

Step-by-step explanation:

[tex]f^{-1}[/tex] means they want you to find the inverse function of y=1/9 x-2.

The inverse is just a swapping of x and y.

People tend to remake the y part the subject again because they want to write it as a function.

Let's start:

[tex]y=\frac{1}{9}x-2[/tex]

Swap x and y:

[tex]x=\frac{1}{9}y-2[/tex]

Now it's time to solve for y:

Add 2 on both sides:

[tex]x+2=\frac{1}{9}y[/tex]

Multiply both sides by 9:

[tex]9(x+2)=y[/tex]

Distribute:

[tex]9x+18=y[/tex]

So The inverse function is:

[tex]f^{-1}(x)=9x+18[/tex]